Inhibition of transcriptional regulation of detoxification genes contributes to insecticide resistance management in Spodoptera exigua - Bo Hu; Yuping Deng; Tao Lu; Miaomiao Ren; Kuitun Liu; Cong Rao; Hailiang Guo; Jianya Su (Communications Biology)
Abstract Synthetic insecticides have been widely used for the prevention and control of disease vectors and agricultural pests. However, frequent uses of insecticides have resulted in the development of insecticide resistance in these insect pests. The resistance adversely affects the efficacy of insecticides, and seriously reduces the lifespan of insecticides. Therefore, resistance management requires new strategies to suppress insecticide resistance. Here, we confirm that CncC/Maf are the key regulators of various detoxification genes involved in insecticide resistance in Spodoptera exigua. Then, we develop a cell screening platform to identify the natural compound inhibitors of CncC/Maf and determine that sofalcone can act as a CncC/Maf inhibitor in vitro and in vivo. Bioassay results showed that sofalcone significantly enhanced the toxicity (more than 3-fold) of chlorpyrifos and lambda-cyhalothrin against S. exigua larvae. Finally, we demonstrate that sofalcone can greatly improve the susceptibility of S. exigua larvae to insecticides by inhibiting the activity of the ROS/CncC-dependent detoxifying enzymes and downregulating the expression levels of detoxification genes. CncC/Maf inhibitors can be used as broad-spectrum synergists to overcome insecticide resistance in pest populations. Altogether, our results demonstrate that reduced expression of detoxification genes resulting from suppression of transcriptional regulation of these genes contributes to controlling insecticide resistance, which provides a very novel and high-efficiency green resistance management strategy.